2022
DOI: 10.1002/adpr.202200109
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Scalable Near‐Zero‐Index Materials

Abstract: Near-zero-index (NZI) materials are becoming increasingly important for photonic designs because they enable new ways to control light-matter interactions at the nanoscale. Many device prototypes that utilize NZI layers are created under conditions that are tool and laboratory specific, making widespread utilization and scalability of NZI materials difficult. Herein, this limitation is circumvented by using transparent conducting oxides (TCOs) produced from scalable commercial sources. The optical response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In previous research, TCOs from 12 scalable commercial suppliers were utilized to report their ENZ and NZI properties influenced by λ ENZ . 30 Thus, controlling λ ENZ in tunable spectral ranges by stable experiments turns out to be an important issue. It is found that the carrier concentration, plasma frequency, and surface plasmon resonance responses of sputtered ITO films can be engineered through different deposition parameters, 31−33 which gives a useful instruction to further study the ENZ tuning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, TCOs from 12 scalable commercial suppliers were utilized to report their ENZ and NZI properties influenced by λ ENZ . 30 Thus, controlling λ ENZ in tunable spectral ranges by stable experiments turns out to be an important issue. It is found that the carrier concentration, plasma frequency, and surface plasmon resonance responses of sputtered ITO films can be engineered through different deposition parameters, 31−33 which gives a useful instruction to further study the ENZ tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Even the advanced techniques introduced in ref require a series of different samples with subsequential λ ENZ . In previous research, TCOs from 12 scalable commercial suppliers were utilized to report their ENZ and NZI properties influenced by λ ENZ . Thus, controlling λ ENZ in tunable spectral ranges by stable experiments turns out to be an important issue.…”
Section: Introductionmentioning
confidence: 99%